Estudo de condições operacionais na produção de penicilina G acilase por diferentes microrganismos - Oguri, Renata Tieko (2006)
Penicillin G acylase (PGA) is an enzyme of major impact in human health for catalyzing the deacilation of the penicillin G, to yield 6-aminopenicillanic acid (6-APA), key intermediate in the semi-synthetic antibiotics production. Several microorganisms produce PGA, but Bacillus megaterium is capable of secreting it to the medium. PGA from B. megaterium has been studied in DEQ-UFSCar. Xanthomonas campestris presents in your DNA the genetic sequence that codify acylase penicillin and tests with a strain of this microorganism from Departamento de Genética e Evolução da UFSCar showed PGA extracellular production. Studies in PGA production were initiated with the microorganism stored in DEQ-UFSCar. At the same time, strains of X. campestris from Coleção de Culturas Tropical (CCT) and Instituto Agronômico do Paraná (IAPAR) were tested. However, assays with these strains showed little cellular growth and no enzymatic activity. The microorganism reactivated was send to Fundação André Toselo for identification. The result showed that the microorganism was Bacillus megaterium. Therefore, at the same time that realized adaptations tries with the new strain of X. campestris, studies of production operational conditions of PGA were performed with strain of Bacillus megaterium, in shaking flasks and bioreactor, as well the enzyme characterization Germination/ propagation of B. megaterium experiments, at 30°C, carried out in shaking flasks showed that the growth time of microorganism in the inoculum step was 24 hours and maximum specific growth rate was µmáx = 0.33h-1. Assays in shaking flasks were carried out in shaker at 30ºC and 300 rpm intend to determine the most adequate pH for the enzyme production in both, microorganism propagation phase and enzyme production phase The results showed that the best pHs among the tested ones were pH 8.0 and 7.0, for the propagation and production phases, respectively, with 355 IU/L. The culture medium with preferentially consumed amino acids 20,0 g/L, potassium phenylacetate 3,5 g/L, solution with differents salts 0,22 g/L and cheese whey 20,0 g/L was the more efficient in PGA production, carried out maximum cellular growth and enzymatic activity, 4,59 g/L and 592UI/L, respectively, in 36 hours. Assays in a 2-L bioreactor, with production medium in the presence of amino acids preferably consumed 10.0 g/L, cheese whey 20.0 g/L, solution of salts 0.22 g/L and inducer potassium phenylacetate 3.5 g/L, indicated that the addition of nutrients during the fermentation is a efficient strategy, providing enzyme production increase. In the study of the influence of oxygen dissolved, carried out in bioreactor too, maximum enzymatic activity was 451 IU/L with 10% of saturation. Moreover, the maximum enzyme production was observed in the bioreactor and not in shaking flasks, like in all experiments until this. In the stage of characterization of the penicillin G acylase from Bacillus megaterium, optimum values of temperature and pH were, 47°C and 8.0, respectively. The Michaelis Menten model fitted resulting in estimated Km and Vmáx parameters values of 1.51 mM and 1.1*10-3 mmol/min*IU, respectively. The activation energy estimated was 27.12 KJ/mol.The results showed that PGA from Bacillus megaterium deactivate completely after 45 minutes of incubation at 60°C and 90 minutes in pH 11.0.